Peran Konselor dalam Perspektif Hadist Akhir Zaman - Muhammad Andri Setiawan (Indonesian Journal of Educational Counseling, 2020)
THE ROLE OF COUNSELOR IN THE PERSPECTIVE OF AKHIR ZAMAN HADITH. This literature review addresses the role of the counselor by pressing on a number of common phenomena that occur today. This phenomenon turns out to correspond to a number of “akhir zaman” hadiths. Of course, with this description, you will increasingly realize that the role of counselor is very much needed now to deal with student dynamics. The ‘akhir zaman’ characters in question include: (1) aspects of humanitarian setbacks caused by drugs; (2) the fading of the tradition of family life and social interaction tends to be individualistic, thus requiring solutions to Islamic values ​​and norms themselves but should be structured by involving school components reflected in the school's vision and mission; (3) the choice of social context needs to be formulated in depth which places the teachings of Islam as a whole without compromising the teachings of Islam as a religion of da'wah; and finally, (4) massive relationships that emphasize strong interpersonal relationships between counselors and students and subject teachers.